Candidate Gene Expression in Bos indicus Ovarian Tissues: Prepubertal and Postpubertal Heifers in Diestrus - Weller, Mayara Morena Del Cambre Amaral; Fortes, Marina Rufino S.; Porto-Neto, Laercio R.; Kelly, Matthew; Venus, Bronwyn; Kidd, Lisa; do Rego, João Paulo Arcelino; Edwards, Sophia; Boe-Hansen, Gry B.; Piper, Emily; Lehnert, Sigrid A.; Guimarães, Simone Eliza Facioni; et al. (Frontiers in Veterinary Science, 2016)
Growth factors such as bone morphogenetic proteins 6, 7, 15 and two isoforms of transforming growth factor-beta (BMP6, BMP7, BMP15, TGFB1 and TGFB2) and insulin-like growth factor system act as local regulators of ovarian follicular development. To elucidate if these factors as well as others candidate genes such as estrogen receptor 1 (ESR1), growth differentiation factor 9 (GDF9), follicle stimulating hormone receptor (FSHR), luteinizing hormone receptor (LHR), bone morphogenetic protein receptor, type 2 (BMPR2), type 1 insulin-like growth factor receptor (IGFR1), and key steroidogenic enzymes cytochrome P450 aromatase and 3-β-hydroxysteroid dehydrogenase (CYP19A1 and HSD3B1) could modulate or influence diestrus on the onset of puberty in Brahman heifers, their ovarian mRNA expression was measured before and after puberty (luteal phase). Six post-pubertal (POST) heifers were euthanized on the luteal phase of their second cycle, confirmed by corpus luteum observation, and six pre-pubertal (PRE) heifers were euthanized in the same day. Quantitative real-time PCR analysis showed that the expression of FSHR, BMP7, CYP19A1, IGF1 and IGFR1 mRNA was greater in PRE heifers, when contrasted to POST heifers. The expression of LHR and HSD3B1 was lower in PRE heifers. Differential expression of ovarian genes could be associated with changes in follicular dynamics and different cell populations that have emerged as consequence of puberty and the luteal phase. The emerging hypothesis is that BMP7 and IGF1 are co-expressed and may modulate the expression of FSHR, LHR and IGFR1 and CYP19A1. BMP7 could influence the down-regulation of LHR and up-regulation of FSHR and CYP19A1, which mediates the follicular dynamics in heifer ovaries. Up-regulation of IGF1 expression pre-puberty, compared to post-puberty diestrus, correlates with increased levels FSHR and CYP19A1. Thus, BMP7 and IGF1 may play synergic roles and were predicted to interact, from the expression data (P = 0.07, r = 0.84). The role of these co-expressed genes in puberty and heifers luteal phase merits further research.